A fluorescent chemosensor for Sn2+ and Cu2+ based on a carbazole-containing diarylethene. Issue 16 (2nd February 2017) - Qu, Shengzu; Zheng, Chunhong; Liao, Guanming; Fan, Congbin; Liu, Gang; Pu, Shouzhi
Abstract : A carbazole-containing diarylethene was synthesized. Its fluorescence was enhanced and quenched, respectively, upon addition of Sn 2+ and Cu 2+ over other cations. Moreover, the compound can be applied to detect Sn 2+ and Cu 2+ in natural water sample. Abstract : A novel diarylethene with a carbazole moiety was developed for the highly selective and sensitive detection of Sn 2+ and Cu 2+ in methanol. Its fluorescence was enhanced with a 76 nm blue shift and selective fluorescence quenching occurred upon the addition of Sn 2+ and Cu 2+, respectively, over a wide range of tested cations. The compound formed complexes with Sn 2+ and Cu 2+ in a 1 : 1 stoichiometry and has the detection limits of 1.9 μM and 1.2 μM, respectively. Moreover, the compound can be applied to detect Sn 2+ and Cu 2+ in natural water samples with high accuracy.